1978
DOI: 10.1002/hlca.19780610529
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Imidazole and Hydrocyanic Acid Derivatives on the ‘Possible Prebiotic’ polyphosphate induced peptide synthesis in aqueous solution

Abstract: Glycine in aqueous solutions of trimetaphosphate or linear polyphosphate at pH adjusted to 8.1‐9.0, is condensed at room temperature to diglycine and very small amounts of triglycine. The addition of imidazole increases the yield of triglycine by a factor of almost 10; supplementary addition of magnesium ion does not increase this effect. On the contrary to what has been observed at pH 11.5‐12.0, the addition of sodium cyanide or cyanamide at pH 8.1‐9.0 diminishes strongly the yield of triglycine and to a less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Small amounts of condensed phosphates are emitted in volcanic fumaroles (Yamagata et al 1991), and heating orthophosphate at relatively low temperatures in the presence of ammonia results in a high yield of condensed phosphates (Osterberg and Orgel 1972). Trimetaphosphate (TMP) has been shown to be an active phosphorylating agent for various molecules including amino acids and nucleosides (Schwartz 1969;Rabinowitz and Hampai 1978;Yamagata et al 1991). However, it has also been suggested that condensed phosphates are not likely to be prebiotically abundant materials (Keefe and Miller 1995).…”
Section: Nucleosides Nucleotidesmentioning
confidence: 98%
“…Small amounts of condensed phosphates are emitted in volcanic fumaroles (Yamagata et al 1991), and heating orthophosphate at relatively low temperatures in the presence of ammonia results in a high yield of condensed phosphates (Osterberg and Orgel 1972). Trimetaphosphate (TMP) has been shown to be an active phosphorylating agent for various molecules including amino acids and nucleosides (Schwartz 1969;Rabinowitz and Hampai 1978;Yamagata et al 1991). However, it has also been suggested that condensed phosphates are not likely to be prebiotically abundant materials (Keefe and Miller 1995).…”
Section: Nucleosides Nucleotidesmentioning
confidence: 98%
“…Although polyphosphates are not especially good phosphorylating reagents under prebiotic conditions, they tend to degrade, especially in the presence of divalent cations at high temperatures, to cyclic phosphates such as trimetaphosphate. Trimetaphosphate has been shown to be a phosphorylating agent for various prebiological molecules, including amino acids and nucleosides (Schwartz, 1969;Rabinowitz and Hampai, 1978). Another intriguing possibility is that reactive phosphates were delivered extraterrestrially in the form of phosphide minerals (Pasek and Lauretta, 2005).…”
Section: Phosphatesmentioning
confidence: 99%